A Call Center Model for Fecal Sludge management (FSM) for Ghana - CGIAR Research Program on Water, Land and Ecosystems (2021)
As part of an agreement for proper disposal of fecal sludge in Tamale, Ghana, a call center is being established to support its enforcement If successful this will be rolled out to other cities